Phase composition evolution of co-precipitated zirconium and yttrium hydroxides during heat treatment - Gabelkov, S.V.; Tarasov, R.V.; Poltavtsev, N.S.; Belkin, F.V. (Functional Materials, 2009)
Formation of complex amorphous hydroxide at co-precipitation of zirconium and yttrium hydroxides has been investigated by X-ray phase analysis and thermal analysis. Its thermal decomposition occurs in a single stage in the temperature interval 20-400°C and results in formation of amorphous zirconia. Parameters of amorphous zirconia "halo" are determined and absence of their dependence on the precursor compound and mass content of yttrium oxide is established. Crystallization temperature of amorphous zirconia (500 to 600°C), average size of coherent-scattering region (28±3 nm) and crystal structure of the phase obtained have been determined. The phase composition evolution depending on heat treatment temperature has been traced in the sequence complex amorphous zirconium/yttrium hydroxide amorphous zirconia - tetragonal zirconia. In this case yttrium, while not forming independent phases, is successively a component of complex amorphous hydroxide, amorphous oxide and tetragonal zirconia. Формування складного аморфного гідроксиду при спільному осадженні гідроксидів цирконію та ітрію досліджено методами рентгенівського фазового та термічного аналізів. Його термічний розклад проходить в одну стадію в інтервалі температур 20-400°С і завершується формуванням аморфного оксиду цирконію. Визначено параметри "гало" аморфного оксиду цирконію та встановлено відсутність їх залежності від сполуки-попередника та масового вмісту оксиду ітрію. Визначено температуру кристалізації аморфного оксиду (500-600°С), середній розмір областей когерентного розсіювання (28±3 нм) і структуру отриманої кристалічної фази. У залежності від температури термообробки простежено еволюцію фазового складу у низці: складний аморфний гідроксид цирконію та ітрію - аморфний оксид - тетрагональний оксид цирконію. При цьому ітрій, не утворюючи самостійних фаз, послідовно входить до складного аморфного гідроксиду, аморфного оксиду та тетрагонального оксиду цирконію. Исследовано формирование сложного аморфного гидроксида при совместном осаждении гидроксидов циркония и иттрия методами рентгеновского фазового и термического анализов. Его термическое разложение проходит в одну стадию в интервале температур 20-400°С и завершается формированием аморфного оксида циркония. Определены параметры "гало" аморфного оксида циркония и установлено отсутствие их зависимости от соединения-предшественника и массового содержания оксида иттрия. Определены температура кристаллизации аморфного оксида (500-600°С), средний размер областей когерентного рассеяния (28±3 нм) и структура полученной кристаллической фазы. В зависимости от температуры термообработки прослежена эволюция фазового состава в ряду: сложный аморфный гидроксид циркония/иттрия - аморфный оксид - тетрагональный оксид циркония. При этом иттрий, не образуя самостоятельных фаз, последовательно входит в состав сложного аморфного гидроксида, аморфного оксида и тетрагонального оксида циркония.